An Exploratory Study on Women Entrepreneurial Motivationin in the Context of Boko Haram Insurgency in North Eastern Nigeria - Rohaya, Mohd Nor; Ashemi, Baba Ali (Human Resource Management Academic Research Society, 2022)
This paper aims to investigate the drivers for women entrepreneurship in the context of BokoHaram insurgency in North East Nigeria. It applies pull-push theory to women entrepreneurial motivation in a violent conflict context. A semi-structured interview was conducted with a total number of 12 women entrepreneurs who were purposely selected among Internally Displaced Persons (IDPs) in the region. The results revealed that majority of the women were driven by the urgent need for survival and livelihood which forms part of a push motivational factor. The finding also shows that previous business experience has contributed to the successful business start-ups despite the challenges these displaced women are facing in the camp. Gender-related challenges were minimal but, the paper recommended for more gender-specific programs in order to reduce the sufferings of the most vulnerable persons particularly women-headed households in post-conflict transition.